The Environmental Performance, Carbon Performance, and Green Innovation: Impact on Carbon Emission Disclosure - Khalisah Oktavia; Husnah Nur Laela Ermaya (EQUITY, 2026)
This study was designed to empirically test the influence of environmental performance, carbon performance, and green innovation on carbon emission disclosure with profitability and firm age as control variables. The research was conducted on companies in the basic materials sector listed on the Indonesia Stock Exchange during the 2022-2024 period with a total sample of 96 observations from 32 companies. This study used a quantitative approach with multiple linear regression analysis using STATA v.17 software. This study found that environmental performance and green innovation have a positive effect on carbon emission disclosure, but carbon performance has no effect on carbon emission disclosure. In addition, the control variables show that profitability has no effect on carbon emission disclosure, while firm age has a positive effect.